Penerapan Etika Bisnis Islam dalam Penjualan Roti Krispi: Konsep dan Implementasi - Syariah Hafizhoh; Desi Sabtina; Rina Susanti; Salamat Riadi; Putri Rahayu; Frezzi Ramadhan; Bilal Hafis; Habibie Ramadhan; Siti Nurjannah (Student Research Journal, 2023)
This journal examines the application of Islamic business ethics in selling crispy bread with the aim of analyzing the concept and its implementation. This research involves a case study on the business of selling sharia-based crispy bread. The results of the study show that the application of the principles of Islamic business ethics, such as honesty, integrity, and a balance between material and spiritual aspects, has a positive impact on the operations and finances of the business. Discussion of the research findings includes evaluating the successful implementation of Islamic business ethics, the challenges faced, and the long-term benefits of this implementation. This research contributes to Muslim entrepreneurs by providing an in-depth understanding of the importance of applying Islamic business ethics in selling crispy bread, as well as practical recommendations for achieving sustainable business success in the context of sharia.